2022
DOI: 10.1093/mtomcs/mfac006
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and uptake of copper via a small copper carrier in blood fluid

Abstract: Studies with Wilson disease model mice that accumulate excessive copper, due to a dysfunctional ATP7B ‘copper pump’ resulting in decreased biliary excretion, showed that the compensatory increase in urinary copper loss was due to a small copper carrier (∼1kDa) (SCC). We show here that SCC is also present in the blood plasma of normal and Wilson disease model mice and dogs, as determined by ultrafiltration and size exclusion chromatography (SEC). It is secreted by cultured hepatic and enterocytic cells, as dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…The metal is distributed throughout the body via the bloodstream, and 0.75–1.4 mg/L Cu 2+ can be found in human serum 3,4 . Approximately 70–90% thereof is contained in ceruloplasmin (CP), while the remaining Cu 2+ , which is typically being referred to as loosely bound Cu 2+ , is associated with albumin (10–15%), α-macroglobulin (5–15%), clotting factors, enzymes (superoxide dismutase (SOD), Oxidases), metallothionein, as well as small Cu 2+ carriers 3 5 . The loosely bound Cu 2+ species comprises the whole amount of serum Cu 2+ that is not bound to CP, whereas so-called labile Cu 2+ represents a smaller subset of the loosely bound pool and is defined only to be in equilibrium with low molecular weight (LMW) ligands, e.g., amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The metal is distributed throughout the body via the bloodstream, and 0.75–1.4 mg/L Cu 2+ can be found in human serum 3,4 . Approximately 70–90% thereof is contained in ceruloplasmin (CP), while the remaining Cu 2+ , which is typically being referred to as loosely bound Cu 2+ , is associated with albumin (10–15%), α-macroglobulin (5–15%), clotting factors, enzymes (superoxide dismutase (SOD), Oxidases), metallothionein, as well as small Cu 2+ carriers 3 5 . The loosely bound Cu 2+ species comprises the whole amount of serum Cu 2+ that is not bound to CP, whereas so-called labile Cu 2+ represents a smaller subset of the loosely bound pool and is defined only to be in equilibrium with low molecular weight (LMW) ligands, e.g., amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is implicated in several biological processes, with the literature describing manganese deficiencies as uncommon but holding a concern for the association of cancer susceptibility with low Mn-dependent superoxide dismutase activity. A vegetarian lifestyle prevents Mn deficiency though it might lead to iron deficiency [ 44 ], which in turn may lead to anemia, and copper build-up in the duodenal epithelium and liver [ 45 ]. Copper is predominantly found in the human brain, being absorbed in the intestine and excreted through bile [ 46 ]; moreover, it has been identified as a potential therapeutic target for obesity and nonalcoholic fatty liver disease (NAFLD), Alzheimer’s disease (AD), and Parkinson’s disease (PD), among others [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process cannot be inhibited by an endocytosis inhibitor or an excess of metal ions taken up by divalent metal transporter 1, indicating alternative pathways to excreting excess Cu. [ 26 ] Furthermore, a recent study showed that a localized lysosome copper transporter, SLC46A3, can modulate intracellular copper levels by sequestering copper in lysosomes, [ 27 ] which demonstrated a new copper‐regulated pathway in cells (Figure 1).…”
Section: Copper Homeostasismentioning
confidence: 99%